Assessment of Top of Atmosphere, Atmospheric and Surface Energy Budgets in CMIP6 Models on Regional Scales. Issue 4 (5th April 2023) - Li, Donghao; Folini, Doris; Wild, Martin
Abstract: We examine top of atmosphere (TOA), atmospheric, and surface energy budget components of 53 CMIP6 models for the period 2000–2009 on regional scales with respect to two reference data sets: the NASA Energy and Water cycle Study (NEWS), from which we adopt the regional decomposition, and the Clouds and the Earth's Radiant Energy System (CERES) Energy Balanced and Filled (EBAF). Focusing on regional scale, CMIP6 models tend to have more energy entering or less energy leaving the climate systems at TOA over the Northern Hemisphere land, Southern Hemisphere ocean and the polar regions compared to CERES EBAF, while the contrary applies in other regions. Atmospheric net shortwave and longwave fluxes both tend to be underestimated in CMIP6 models as compared to EBAF, with substantial regional differences. Regional surface radiative fluxes as reported by NEWS and EBAF can differ substantially. Nevertheless, robust regional biases exist in CMIP6. Surface upward shortwave radiation is overestimated by 43 (81%) models over Eurasia. For almost all surface radiative flux components over the North Atlantic and Indian Ocean, there are at least 21 (40%) models which fall outside the NEWS uncertainty range. Latent heat flux is overestimated over most of the land and ocean regions while firm conclusions for sensible heat flux remain elusive due to discrepancies between different reference data sets. Compared to CMIP5, there is an overall improvement in CMIP6 on regional scale. Still, substantial deficiencies and spreads on regional scale remain, which are potentially translated into an inadequate simulation of atmospheric dynamics or hydrological cycle. Plain Language Summary: The Earth's energy budget is the principal determinant of climate on our planet and is shaped by the balance between the solar energy absorbed by the Earth and the thermal energy that leaves Earth to space. The ability of Earth System Models (ESMs) to simulate the Earth's energy budget on global scale has been widely assessed in previous studies. In the present study, their ability to simulate the energy budgets on regional scales are examined in detail and compared with reference data sets and their previous model generation. Our study finds that models tend to receive more energy or lose less energy at the top of atmosphere over Northern Hemispheric land, Southern Hemispheric ocean, and polar regions. The net energy fluxes within the atmosphere are also underestimated with substantial differences between regions. In most models, some energy fluxes at the surface of the Earth are even out of the references' uncertainty range in regions such as Eurasia, the North Atlantic, and Indian Oceans. Nevertheless, compared to their previous generation, the state‐of‐the‐art ESMs investigated in our study show an overall improvement in their regional energy budgets, but deficiencies in atmospheric dynamics and hydrological cycle on regional scales should not be neglected. Key Points: This study investigates the regional energy budgets in CMIP6 models, and compares them with reference data sets and CMIP5 models In most models, some energy budget components are out of the references' uncertainty range in some regions The regional scale energy budgets simulated by the CMIP6 models are overall improved compared to CMIP5